Co-existence of Two Rare Conditions: Oculo-Palato-Cerebral Syndrome and Congenital Chylothorax - Seyhan Erisir Oygucu; Gonul Tezel; Muhammet Kazim Erol; Ozgur Erkal (Mashhad University of Medical Sciences, 2018)
Background: Oculo-palato-cerebral syndrome is an extremely rare condition characterized by various features, including low-birth weight, microcephaly, cerebral atrophy, mild-to-severe developmental delay, cleft palate, persistent hyperplastic primary vitreous, microphthalmia, small hands and feet, joint laxity, and large ears with thick helices. Diagnosis of this syndrome is based on the clinical manifestations, particularly the presence of persistent hyperplastic primary vitreous in association with other malformations. Congenital chylothorax is also a rare condition in the neonatal period, which is caused by the abnormal accumulation of the lymphatic fluid within the pleural space. This condition may be detected prenatally or during the neonatal period.  Case report: We presented the case of a patient with oculo-palato-cerebral syndrome and congenital chylothorax based on a literature review. Conclusion: Oculo-palato-cerebral syndrome and congenital chylothorax are both rare conditions. To the best of our knowledge, this was the first case report on congenital chylothorax in association with oculo-palato-cerebral syndrome in the available literature. Since there have only been five case reports on these patients, further evidence is required to confirm the possible association between these rare conditions.